2020
DOI: 10.7554/elife.56655
|View full text |Cite|
|
Sign up to set email alerts
|

Intravascular flow stimulates PKD2 (polycystin-2) channels in endothelial cells to reduce blood pressure

Abstract: PKD2 (polycystin-2, TRPP1), a TRP polycystin channel, is expressed in endothelial cells (ECs), but its physiological functions in this cell type are unclear. Here, we generated inducible, EC-specific Pkd2 knockout mice to examine vascular functions of PKD2. Data show that a broad range of intravascular flow rates stimulate EC PKD2 channels, producing vasodilation. Flow-mediated PKD2 channel activation leads to calcium influx that activates SK/IK channels and eNOS serine 1176 phosphorylation in ECs. These signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 66 publications
4
70
0
Order By: Relevance
“…Peripheral endothelial cells and BECs express receptors to respond to several extracellular stimuli like chemical transmitters, stretching, mechanical force, temperature, osmotic pressure and pH changes, most of them coupled to G‐protein coupled receptors that activate second messenger pathways that involve [Ca 2+ ] i mobilization from internal stores 9,10,14,35 . We found that shifting the perfusion line to apply different drugs to BECs produced a transient [Ca 2+ ] i response, which could be generated by the expression of mechanical‐activated receptors coupled to [Ca 2+ ] i dynamics 35 . For instance, TRPV5 and TRPV6 channels are constitutively open, are highly permeable to Ca 2+ and are widely expressed in the brain, 36 although their expression has not been yet demonstrated in BECs.…”
Section: Discussionmentioning
confidence: 88%
“…Peripheral endothelial cells and BECs express receptors to respond to several extracellular stimuli like chemical transmitters, stretching, mechanical force, temperature, osmotic pressure and pH changes, most of them coupled to G‐protein coupled receptors that activate second messenger pathways that involve [Ca 2+ ] i mobilization from internal stores 9,10,14,35 . We found that shifting the perfusion line to apply different drugs to BECs produced a transient [Ca 2+ ] i response, which could be generated by the expression of mechanical‐activated receptors coupled to [Ca 2+ ] i dynamics 35 . For instance, TRPV5 and TRPV6 channels are constitutively open, are highly permeable to Ca 2+ and are widely expressed in the brain, 36 although their expression has not been yet demonstrated in BECs.…”
Section: Discussionmentioning
confidence: 88%
“…In this regard, TRPA1 and TRPV3 channels have been shown to be important Ca 2+ influx pathways in arterial endothelium from other vascular beds [34, 38]. Moreover, TRPP1 channels were recently proposed as an endothelial Ca 2+ influx pathway that mediates flow-induced vasodilation [39]. Whether TRPA1/TRPV3/TRPP1 channels are functional in venous endothelium has not been investigated.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…2 Notably, polycystin 1 and 2 are expressed in vascular endothelial and vascular smooth muscle cells. 3,4 Primary cilia defects that characterize ADPKD are associated with dysfunction in endothelial cilia, affecting calcium and nitric oxide signaling that can consequentially lead to vascular disorders such as hypertension. 5 Hypertension occurs in greater than 60% of individuals with ADPKD before the loss of kidney function, resulting in a much earlier diagnosis of hypertension than the general population and is closely associated with TKV.…”
Section: Introductionmentioning
confidence: 99%